2021
DOI: 10.3389/fendo.2021.796661
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Metabolic Recuperation After Weight Loss in High Fat Diet-Induced Obese Mice

Abstract: Dietary intervention is a common tactic employed to curtail the current obesity epidemic. Changes in nutritional status alter metabolic hormones such as insulin or leptin, as well as the insulin-like growth factor (IGF) system, but little is known about restoration of these parameters after weight loss in obese subjects and if this differs between the sexes, especially regarding the IGF system. Here male and female mice received a high fat diet (HFD) or chow for 8 weeks, then half of the HFD mice were changed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 84 publications
6
6
0
Order By: Relevance
“…Another interesting finding of the present study was the differential effect of CAFR diet on decreasing BWG in females but not in males, despite CAFR females maintaining a higher proportion of non-chow food intake than CAFR males. It has been previously reported in mice that, when switching from HFD to chow, females lose body weight faster than males [ 55 ], which is in accordance with our results, since our animals were switched from CAF to CAFR diet, which increased chow intake. The CAFR diet shifted the intake of the animals toward a healthier profile that included increased chow intake, which is considered a healthier food choice than CAF, and decreased cafeteria diet intake in both sexes, which is consistent with previous observations in animals fed this diet [ 29 , 56 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Another interesting finding of the present study was the differential effect of CAFR diet on decreasing BWG in females but not in males, despite CAFR females maintaining a higher proportion of non-chow food intake than CAFR males. It has been previously reported in mice that, when switching from HFD to chow, females lose body weight faster than males [ 55 ], which is in accordance with our results, since our animals were switched from CAF to CAFR diet, which increased chow intake. The CAFR diet shifted the intake of the animals toward a healthier profile that included increased chow intake, which is considered a healthier food choice than CAF, and decreased cafeteria diet intake in both sexes, which is consistent with previous observations in animals fed this diet [ 29 , 56 ].…”
Section: Discussionsupporting
confidence: 93%
“…This might be explained by the fact that females presented a higher CAF intake and a lower chow intake than males, which has also been reported in a model of high-fat diet (HFD) [ 54 ]. Previous studies reported that rodent males under HFD gained body weight more rapidly than females, which presented a delayed response [ 54 , 55 ]. These results partially contrast with ours; however, the fact that these studies used a HFD while ours used the CAF diet might partially explain the different results we obtained here.…”
Section: Discussionmentioning
confidence: 99%
“…There were no significant differences observed in terms of body weight or food consumption between the HFD-fed Lcn2 −/− male mice and WT mice, as well as between the ND-fed Lcn2 −/− female mice and WT mice. This is consistent with the findings of numerous rodent studies, which have shown that males are typically more vulnerable to the negative effects of HFD [2,25]. Lcn2 acts as a satiety signal, and its rise allies with a decrease in hunger.…”
Section: Discussionsupporting
confidence: 91%
“…One caveat that must be taken into consideration is that the intake of HFD was compared to that of an LFD; although this diet has been commercialized as a control diet to be used in conjunction with the HFD, it has a higher level of carbohydrates than a normal rodent chow diet. This diet also has some metabolic effects when compared to chow intake (Guerra-Cantera et al, 2021 ). Another limitation of the study is that it was not designed for a strict metabolic study, where the animals are usually individually caged, allowing the food intake to be singly monitored.…”
Section: Discussionmentioning
confidence: 99%